A first-principles study of sodium adsorption and diffusion on phosphorene1. Issue 25 (7th July 2015) - Liu, Xiao; Wen, Yanwei; Chen, Zhengzheng; Shan, Bin; Chen, Rong
<x xml:space="preserve">Abstract</x> The structural, electronic, electrochemical as well as the diffusion properties of Na doped phosphorene have been investigated, which indicates that the phosphorene could be a promising sodium-ion battery anode based on a first-principles study.